1999
DOI: 10.1111/j.1559-1816.1999.tb02295.x
|View full text |Cite
|
Sign up to set email alerts
|

Attributions for Poverty: A Comparison of Middle‐Class and Welfare Recipient Attitudes1

Abstract: This study compared how a nonrandom sample of 112 middle‐class persons and 124 welfare recipients explained poverty and perceived the welfare system and welfare recipients. Analyses revealed that welfare recipients were more likely to make structural attributions for poverty and to reject restrictive welfare‐reform policies. However, they were also more likely than middle‐class respondents to regard welfare recipients as dishonest and idle. Both groups underestimated the percentage of European Americans receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
195
5
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(233 citation statements)
references
References 28 publications
19
195
5
10
Order By: Relevance
“…Specifically, because the core principles of conservatism centre on (a) opposition to change and (b) acceptance of inequality (see Jost, Glaser, Kruglanski, & Sulloway, 2003), conservatives should be more likely than liberals to locate the cause of poverty within the person and to view one's destitute status as personally controllable (also see Zucker & Weiner, 1993). Accordingly, research shows that political conservatism is positively associated with attributions that are unsympathetic to the poor (see Bullock, 1999;Cozzarelli et al, 2001;Hine & Montiel, 1999;Hopkins, 2009;Skitka, 1999). Therefore, we predict that participants' level of conservatism will correlate with membership in latent profiles marked by high levels of internal and personally controllable attributions for poverty.…”
Section: Hypothesesmentioning
confidence: 87%
See 1 more Smart Citation
“…Specifically, because the core principles of conservatism centre on (a) opposition to change and (b) acceptance of inequality (see Jost, Glaser, Kruglanski, & Sulloway, 2003), conservatives should be more likely than liberals to locate the cause of poverty within the person and to view one's destitute status as personally controllable (also see Zucker & Weiner, 1993). Accordingly, research shows that political conservatism is positively associated with attributions that are unsympathetic to the poor (see Bullock, 1999;Cozzarelli et al, 2001;Hine & Montiel, 1999;Hopkins, 2009;Skitka, 1999). Therefore, we predict that participants' level of conservatism will correlate with membership in latent profiles marked by high levels of internal and personally controllable attributions for poverty.…”
Section: Hypothesesmentioning
confidence: 87%
“…Levels of political conservatism also positively correlate with people's tendency to make internal attributions (Cozzarelli, Wilkinson, & Tagler, 2001;Hine & Montiel, 1999;Shirazi & Biel, 2005;Zucker & Weiner, 1993). Structural and fate-based attributions, however, tend to be made by the poor (Bullock, 1999;Furnham, 1982a;Kluegel & Smith, 1986;Morçöl, 1997;Niemela, 2008). Thus, demographic variables are associated with people's attributions for poverty.…”
Section: Attributions For Povertymentioning
confidence: 97%
“…Another negative belief about the poor is that they are dishonest. For example, one common notion of welfare recipients is that they spend their money on drinking and drugs (Bullock, 1999;Underlid, 2005). Similar examples are extensive and widespread: The stereotype of the poor includes unfavorable individual properties, such as having low intelligence, being lazy, and not being interested in self-improvement (see e.g.…”
Section: Stereotypes Of the Poormentioning
confidence: 99%
“…As a consequence, welfare recipients sense that society sees them as criminals, "milking the system. " (Underlid, 2005) Although the content of the stereotype of poor people as outlined in earlier research primarily originates from North American studies (as in Bullock, 1999;Cozzarelli et al, 2001;Gilmore & Harris, 2008;Henry, Reyna, & Weiner, 2004;Kluegel & Smith, 1986;Woods et al, 2005), researchers have identified similar stereotype content across post-communist countries, such as Hungary and Russia, where the acceptance of inequality and poverty seems to be lower than in the United States (Kreidl, 2000).…”
Section: Stereotypes Of the Poormentioning
confidence: 99%
“…There are scattered researches on professional ethics such a research by Posner and Schmidt which showed that professional ethics is not seen among lower managers compared to higher level ones (Posner and Schmidt, 1987;Andrisani, 1978;Anderson, 1995). There was no difference between poor and rich people in respecting professional ethics (Bullock, 1999;. Hegarty and Sims (1979) clarified that the organizations should devise some formal and informal policies to support ethical behaviors in order to increase respecting ethical principles (Hegarty and et al, 1979).…”
Section: Professional Ethicsmentioning
confidence: 99%